Colonization and agricultural policy in the province of Buenos Aires. Sectoral demands and official responses during the first half of the 20th century - Blanco, Monica (Centro de Historia Argentina y Americana, 2014)
The changing internal and external conditions began to affect the development of the agro-exporting model, during the early decades of the 20th century, put the "land question" in the center of discussion on the model of desirable country. If the concentration of the ownership of the land began to be viewed as a cause of the major evils that concerned society, agricultural colonization was raised as the way to overcome the contradictions affecting the growth of the sector. In this work, we have sought to account for some of the expressions for the implementation of this type of agricultural policies paying particular attention in the Buenos Aires case